DIGITAL EURO AS NEXT EVOLUTION OF THE EUROPEAN CURRENCY - UNGUREANU, DRAGOS ADRIAN (Annals of Spiru Haret University. Economic Series, 2022)
Digitalisation has spread to every corner of our lives and transformed how we pay. In this new era, a digital euro would guarantee that citizens in the euro area can maintain costless access to a simple, universally accepted, safe and trusted means of payment. A digital euro would not replace cash, but rather complement it. The Eurosystem will continue to ensure the access to cash across the euro area. A digital euro would give an additional choice about how to pay and make it easier to do so, contributing to accessibility and inclusion. It would support the digitalisation of the European economy and actively encourage innovation in retail payments.